TOLERANSI BERAGAMA PADA SISWA SMA: HUBUNGAN ANTARA INTELLECTUAL HUMILITY DAN TOLERANSI BERAGAMA - Soraya Arifianti; Eva Septiana (Departemen Psikologi Universitas Pendidikan Indonesia, 2021)
AbstractNowadays, various surveys have found a tendency of religious intolerance in educational institutions, especially high schools. The tendency of religious intolerance includes practices, views, and opinions. This indication is feared to develop into radical tendencies and actions. Recent research also shows the significance of intellectual humility as a virtue to promote positive attitudes such as religious tolerance. This study aims to determine the relationship between intellectual humility (IH) with religious tolerance in high school students. The research approach used is quantitative with the correlation method. The number of participants in the study was 365 students who were determined through convenient sampling. Instruments used in this study are Religious Tolerance Measurement and Comprehensive Intellectual Humility Scale (CIHS). The results showed that there was a significant positive correlation between IH and religious tolerance, r (.13). These results indicate that the level of correlation that occurs between Intellectual Humility and students' religious tolerance is low. This means that even though the two variables are related, the increase in the IH score in students only slightly increases the value of religious tolerance in students. AbstrakDewasa ini, berbagai survei menemukan kecenderungan intoleransi beragama di institusi pendidikan, terutama SMA. Kecenderungan intoleransi beragama tersebut meliputi praktik, pandangan, dan opini. Jika dibiarkan, indikasi tersebut dikhawatirkan berkembang menjadi sikap dan aksi radikal. Beberapa penelitian terbaru menunjukkan bahwa intellectual humility mempengaruhi toleransi beragama. Penelitian ini bertujuan untuk mengetahui hubungan antara intellectual humility (IH) dengan toleransi beragama pada siswa SMA. Pendekatan penelitian yang dipergunakan adalah kuantitatif dengan metode korelasi. Partisipan penelitian berjumlah 365 orang siswa yang ditentukan melalui convenient sampling. Alat ukur yang digunakan Religious Tolerance Measurement dan Comprehensive Intellectual Humility Scale (CIHS). Hasil penelitian menunjukkan bahwa terdapat korelasi positif yang signifikan antara IH dan toleransi beragama sebesar 0.13. Hasil ini menunjukkan bahwa pada dasarnya tingkat korelasi yang terjadi antara Intellectual Humility dan toleransi beragama siswa rendah. Artinya, meskipun kedua variabel tersebut berhubungan, kenaikan nilai IH pada siswa hanya sedikit menaikkan nilai toleransi beragama pada siswa.